(untitled) (Research, Society and Development, 2021)
The present study aimed to report the experience of an operative group with obese diabetics of a family health strategy. This is an experience report, conducted with obese diabetic patients of a Basic Health Unit (UBS) in the city of Caxias, Maranhão, Brazil, from May to August 2019. Ten users with type 2 DM, female, aged 37 to 76 years and diagnosed with grade I, II and III obesity participated of the activities. Five one-hour meetings were held on topics related to health and quality of life. The themes addressed in the operating groups were: Knowing the chronic condition; Approach to what is lifestyle; Integrality and multidimensionality of health; Self-care and autonomy and Life plan. The operating groups enabled the active participation of all. Thus, these groups were directed to obese diabetics who sought behavioral changes.The group interaction promoted an opportune environment, free of prejudice and stigmas, which motivated diabetics to change their lifestyle, especially with regard to body weight control.